PERANCANGAN UI/UX SISTEM INFORMASI CERDAS UNTUK MONITORING PERTUMBUHAN DAN PREDIKSI PANEN MANGGA BERBASIS WEB: UI/UX Design of an Intelligent Information System for Web-Based Mango Growth Monitoring and Harvest Prediction - Dian Pramadhana; Darsih; Riyan Farismana (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Mango is one of Indonesia's leading horticultural commodities with high economic value and significant potential to support the productivity of the agricultural sector. However, monitoring plant growth, recording plant development, and scheduling harvest activities in most mango plantations are still carried out manually, resulting in fragmented information and increasing the risk of inaccurate harvest timing. This study aims to design the User Interface (UI) and User Experience (UX) of a web-based Intelligent Information System for Mango Growth Monitoring and Harvest Prediction using the Design Thinking method. The proposed method consists of five stages, namely Empathize, Define, Ideate, Prototype, and Testing, which emphasize a user-centered approach to developing an intuitive and user-friendly interface. The results of this study produced a web-based prototype consisting of five main interfaces: Dashboard, Plant Monitoring, Harvest Prediction, Harvest Calendar, and Reports. Each interface was designed to support plant growth monitoring, harvest prediction, harvest schedule management, and integrated reporting of harvest activities. The proposed UI/UX design is expected to serve as a reference for developing a more effective mango monitoring and harvest prediction information system, improve system usability, and support decision-making in mango plantation management.